The ethics of everyday medicine : explorations of justice - Montgomery, Erwin B., Jr (Academic Press, 2021)
"Ethics of Everyday Medicine: Explorations of Justice examines and analyses the relatively unexplored domain of ethics involved in the everyday practice of medicine. From the author's clinical experience, virtually every decision made in the day-to-day practice of medicine is fundamentally an ethical question, as virtually every decision hinges on some value judgment that goes beyond the medical facts of the matter. ... Ethics of Everyday Medicine: Explorations of Justice acknowledges that there are no answers yet to the ethical dilemmas that confront the everyday practice of medicine, but proposes a framework for deeper analysis and action. This reading would be useful to all healthcare professionals. Regulators and policy makers could also benefit from understanding how the complex healthcare environment influences medical decisions at point of care. Offers an overview of the current health care ecosystem and the ethical questions posed by divergent interests. Includes cases for ethical analysis of common medical practice. Proposes a framework for ethical decision making in the clinical setting. Provides critical analysis of Reflective Equilibrium and ethical induction from the perspective of logic and statistics."--Publisher